A sport leader's attempt to foster a coaches' community of practice - Culver, D. M.; Trudel, P.; Werthner, P. (International Journal of Sports Science and Coaching, 2009)
This case study examines a sport leader's attempt to foster a coaches' community of practice in a competitive youth baseball league. It is analysed using Wenger's [8] community of practice framework. Interviews were conducted with seven participants including the sport leader (technical director), the league manager, and five coaches. The retrospective account of time period 1 (covering four years) portrays how a visionary leader instigated changes in the sport culture to have coaches share knowledge with the common goal of developing all of the league athletes. For example, the coaches were selected for their specific expertise and were given the responsibility for the corresponding players not only on their own team but on all teams in the league. Establishing a co-operative environment in a competitive context required strong leadership and presented challenges including the alignment of all the coaches, parents, and referees. The time period 2 (covering three years), also studied retrospectively, demonstrates that the loss of the visionary leader led to the return to a more traditional, competitive environment. Finally, the time period 3 (covering one year), which was the timeframe when the research project was conducted, shows a willingness to return to the collaborative ways of time period 1, but also the challenges in making this happen without the presence of a strong, visionary leader.